2015
DOI: 10.3109/10717544.2015.1039666
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oral bioavailability of insulin-loaded solid lipid nanoparticles: pharmacokinetic bioavailability of insulin-loaded solid lipid nanoparticles in diabetic rats

Abstract: Objective: Insulin is a hormone used in the treatment of diabetes mellitus. Multiple injections of insulin every day may causes pain, allergic reactions at injection site, which lead to low patient compliance. The aim of this work was to develop and evaluate an efficient solid lipid nanoparticle (SLN) carrier for oral delivery of insulin. Methods: SLNs were prepared by double emulsion solvent evaporation (w/o/w) technique, employing glyceryltrimyristate (Dynasan 114) as lipid phase and soy lecithin and polyvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 35 publications
(41 reference statements)
1
52
0
Order By: Relevance
“…In the present study, PK‐PD modelling and non‐compartmental analysis demonstrated that the pharmacokinetic and pharmacodynamic properties of inhaled rh‐insulin microparticles were significantly improved in the presence of PS or PHT. The relative pharmacokinetic bioavailability F (%) and pharmacodynamic availability PA (%) in PS and PHT‐loaded rh‐insulin dry powders were enhanced compared with previously reported inhaled insulin . Generally, rh‐insulin has low bioavailability mostly due to its early degradation before absorption, inactivation and digestion by widely distributed insulin‐degrading enzymes (proteolytic enzymes), poor permeability across mucosal epithelium, high molecular weight and lack of lipophilicity .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In the present study, PK‐PD modelling and non‐compartmental analysis demonstrated that the pharmacokinetic and pharmacodynamic properties of inhaled rh‐insulin microparticles were significantly improved in the presence of PS or PHT. The relative pharmacokinetic bioavailability F (%) and pharmacodynamic availability PA (%) in PS and PHT‐loaded rh‐insulin dry powders were enhanced compared with previously reported inhaled insulin . Generally, rh‐insulin has low bioavailability mostly due to its early degradation before absorption, inactivation and digestion by widely distributed insulin‐degrading enzymes (proteolytic enzymes), poor permeability across mucosal epithelium, high molecular weight and lack of lipophilicity .…”
Section: Discussionmentioning
confidence: 91%
“…The relative pharmacokinetic bioavailability F (%) and pharmacodynamic availability PA (%) in PS and PHT-loaded rhinsulin dry powders were enhanced compared with previously reported inhaled insulin. [5,28,30] Generally, rh-insulin Data represent mean AE SEM (n = 5). T min , time to reach the minimum serum glucose concentration; C min (%), the percentage minimum serum glucose concentration; AAC 0-360 min , area above the curve of reduced serum glucose concentrations; PA, the relative pharmacological availability; k in , the apparent zero-order rate constant for the production of serum glucose, k out , the first-order rate constant for the utilization of serum glucose, IC 50 , the rh-insulin concentration that produces 50% of maximal inhibition on serum glucose production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins and peptides, such as insulin, growth hormones, antibodies and enzymes, are being routinely used for therapeutic purposes (Szlachcic et al, 2011;Ansari et al, 2016). However, in contrast to these advances in protein production and purification techniques, the mode of administration of proteins to patients has remained principally unchanged, based almost solely on injections of the proteins in their native conformation (Narayanaswamy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%